Progress in potential toxicity of chiral pesticides - LIU Wei-ping; ZHANG Ying (浙江大学学报. 农业与生命科学版)
In the past, chiral pesticides were explored as racemic mixtures in environmental fate and ecotoxicities. However, as a result of the enantioselective interactions with chiral molecules, the enantiomers of chiral pesticides may have different potential toxicities to humans and animals. The present review introduced recent findings on enantioselective endocrine disruption, neurotoxicity, immunotoxicity, reproductive and developmental toxicity of organophosphorus, organochlorines, pyrethroids and phenylpyrazole pesticides, as well as the underlying mechanisms. Furthermore, the developmental trends of future investigations were discussed.